"Pelo poder de Zambi e pela força de Oxalá": identidade social entre mães, pais, filhas e filhos de Santo de uma comunidade de Umbanda no estado do Rio de Janeiro - Eleotério, Isabele Santos (2018)
Based on the Social Identity Theory, this thesis aimed to investigate the group membership linked to the identity processes between members of an Umbanda Center in the state of Rio de Janeiro. The option for the study of the Umbandist community was based on the assumption that community life tends to express social identity in a dynamic and contextualized way. Thus, empirical research, of a qualitative and exploratory nature, was carried out by means of an ethnographic research. Three complementary studies were developed: (E1) participant observation in 40 sessions of the Center, involving all members of the community (n = 21); (E2) interviews with six mothers and two fathers of “santo” from the Center (n = 08), aged between 30 and 65 years; and (E3) interviews with eight daughters and five sons of “santo” from the community Center (n = 13), aged between 18 and 70 years. The observations were carried out with the support of a structured field diary and the interviews by means of a semi-structured script. The 21 interviewees were in the Center for a period ranging from two to 10 years. To refine the data for the first study, thematic Content Analysis was used, and the narratives obtained in the second and third studies were analyzed by the Descending Hierarchical Classification (DHC), carried out with the help of Alceste software. The main results found point to the social identity of the members of the Center mainly based on religious activities and intra-family relationships. In general, the organization of the Center and the rituals integrate two systems of references for the faithful: the four matrices of Umbanda (European, Amerindian, African and Eastern) and the seven lines of work (Oxalá, Orixás, Orientais, Pretos Velhos, Caboclos, Crianças mnand Exus). In the first study (E1) were described: the physical space, with the holy and ritualistic places; the organization and preparation of the temple for the sessions; the social space, with the four types of components (priests, entities, mediums and cambonos); as well as the type, preparation and conduct of sessions and other rituals. Showing "The genesis of the composition of the group", "The identity process in the mediumistic relation" and "In- group demarcation" (according to DHC), in the second study (E2), the sense of belonging was highlighted by the fusion between everyday life, family and religion. The investigation carried out with the daughters and the sons of santo (E3), it was possible to identify, through the DHC, two main bulwarks of the dynamics of group membership: "Identity camouflage" and "Effect of assimilation". Were recognized the activities of adherents related to religious formation, self-perception resulting from comparison with catholics and evangelicals, and the prejudice directed at Umbanda. For the purpose of discussing the identity processes in the context of belonging to the Umbanda community, we followed by three main dimensions: (i) social creativity - the formation of the religious community, the Umbanda headquarters and the house lines; (ii) social identity and the two incorporations: identity and mediumship; and (iii) the group process - intergenerational transmission, religious formation and the expansion of relations. It is expected that the study developed may contribute with the body of knowledge produced on the religious phenomenon in the context of the analysis of the psychosocial processes, as well as acting as a resource to help to reduce the prejudice against Umbandist groups.